Extensive Listening in a Colombian University: Process, Product, and Perceptions - Carlos A. Mayora (Asociación Colombiana de Profesores de Ingles, 2017)
The current paper reports an experience implementing a small-scale narrow listening scheme (one of the varieties of extensive listening) with intermediate learners of English as a foreign language in a Colombian university. The paper presents (a) how the scheme was designed and implemented, including materials and procedures (the process); (b) how the students performed in the different activities with an emphasis on time spent watching/listening and their perceptions of video difficulty and self-rated comprehension (the product); and (c) how the students felt and viewed the experience (perception). Product and perceptions showed that the pedagogical implementation was positive which leads to a discussion of a number of implications for this context and similar ones.